Safety culture regarding zoonoses on domestic ruminant farms - Starič, Jože (Array, 2020)
Veterinarians in buiatric practice, alongside veterinary care and animal welfare, are also responsible for protecting assisting personnel and those working on the holding from zoonoses. Therefore, they need to be knowledgeable about common zoonotic diseases of ruminants, in particular, and protection from their contraction. Veterinarians should know which zoonotic diseases are present in their country and neighbouring countries to be prepared to advise. Zoonotic diseases of ruminants often show no typical clinical presentation, so awareness of self-protective behaviour when dealing with animals in the prevention of zoonoses is very important. This article provides a review of the common zoonoses of domestic ruminants in South-East Europe that are transmitted when handling animals, and their manner of transmission to humans. Safety culture in ruminant production relates to employee attitudes and behaviour concerning health and safety, which also has a significant impact on zoonosis prevention. Improving the safety culture among livestock sector workers and worker behaviours that prevent the risk of zoonoses are also discussed.